ChemInform Abstract: Diastereodivergent Synthesis of Trisubstituted Alkenes Through Protodeboronation of Allylic Boronic Esters: Application to the Synthesis of the Californian Red Scale Beetle Pheromone. Issue 20 (25th April 2013) - Hesse, Matthew J.; Butts, Craig P.; Willis, Christine L.; Aggarwal, Varinder K.
Abstract Depending on the protonation conditions either E‐ or Z‐alkenes are selectively obtained from readily accessible allylic boronates.